2016
DOI: 10.1177/0093854816668218
|View full text |Cite
|
Sign up to set email alerts
|

“Contagious Accountability”

Abstract: The use of body-worn cameras (BWCs) by the police is rising. One proposed effect of BWCs is reducing complaints against police, which assumes that BWCs reduce officer noncompliance with procedures, improve suspects’ demeanor, or both, leading to fewer complaints. We report results from a global, multisite randomized controlled trial on whether BWC use reduces citizens’ complaints. Seven discrete tests (N = 1,847 officers), with police shifts as the unit of analysis (N = 4,264), were randomly assigned into trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(47 citation statements)
references
References 106 publications
1
34
0
1
Order By: Relevance
“…A similar behaviour change in the presence of camera equipment was reported by Ariel et al (2016) in a different context. The authors reported that when police were equipped with body-worn cameras the behaviour of both officers and citizens improved, a phenomenon they call "contagious accountability", and fewer complaints were made against the police.…”
Section: Users Reporting Issues Through Video Evidencesupporting
confidence: 83%
“…A similar behaviour change in the presence of camera equipment was reported by Ariel et al (2016) in a different context. The authors reported that when police were equipped with body-worn cameras the behaviour of both officers and citizens improved, a phenomenon they call "contagious accountability", and fewer complaints were made against the police.…”
Section: Users Reporting Issues Through Video Evidencesupporting
confidence: 83%
“…On the one hand, survey research has generally found that officers are receptive to BWCs (Gaub et al, 2020;Jennings et al, 2014;White et al, 2018) because they see BWCs as a form of protection against citizen allegations of misconduct (Goetschel & Peha, 2017;Owens & Finn, 2018;Pelfrey & Keener, 2016). Indeed, with a few exceptions (Ariel, Farrar, & Sutherland, 2015;White et al, 2018), most studies have demonstrated that officers wearing BWCs received significantly fewer complaints than officers not wearing them (Ariel et al, 2017;Braga, Sousa, Coldren, & Rodriguez, 2018;Katz et al, 2014). On the other hand, community surveys indicate that the public is supportive of agencies outfitting their officers with BWCs because they see it as a way to hold police more accountable for disparities in stops, arrests, and uses of force (Sousa et al, 2018;Todak et al, 2018).…”
mentioning
confidence: 99%
“…Research that explores the costs and benefits of body-work camera (BWC) program implementation offer mixed results. Findings suggest the BWCs may reduce civilian complaints against police officers (Ariel, Farrar, & Sutherland, 2015;Ariel et al, 2017) and result in quicker resolution of civilian complaints that are filed and sustained (Katz, Kurtenbach, Choate, & White, 2015). Footage can also be used to enhance training protocols (Coudert, Butin, & Le Métayer, 2015;Willits & Makin, 2018) and pinpoint how evidence-informed policy can be best deployed (Voigt et al, 2017).…”
mentioning
confidence: 99%